In Vitro Activity of HSR-903, a New Oral Quinolone, against Bacteria Causing Respiratory Infections - Watanabe, Akira (American Society for Microbiology, 1999)
The in vitro activity of HSR-903, an oral quinolone, against 196 recent clinical isolates of respiratory pathogens was evaluated. HSR-903 was 2 to 32 times more active than ofloxacin, ciprofloxacin, and sparfloxacin against Staphylococcus aureus, including methicillin-resistant strains, and Streptococcus pneumoniae and was at least as active as the other quinolones against gram-negative pathogens.